(untitled) (Revista Apotheke, 2024)
This study focuses on the intersection between Artificial Intelligence (AI) and contemporary art. It centers on Lev Manovich’s exhibition Unreliable Memories as a case study, aiming to analyze how Manovich uses AI to expand the visual and conceptual boundaries of art, as well as the reliability of synthetic representations produced by these technologies. The document is divided into three main parts. It begins with a comprehensive theoretical contextualization on the aesthetics of AI and the challenges associated with artistic creation using image generation tools. Next, it analyzes the exhibition itself, describing the various series of works, from hand-drawn pieces of the 1980s to recent AI-generated creations – covering specific series such as Drawing Rooms and In the Garden – with visual peculiarities and imperfections that reflect the ephemeral and fragmented nature of memory. Finally, it discusses how the imperfections and peculiarities of AI-generated images reflect the fallibility of memory, challenging traditional perceptual norms. This research provides relevant insights into AI Aesthetics for the artistic and academic community, laying the groundwork for future academic and artistic investigations in the field.